The decline of the caste question : - Sen, Dwaipayan (Cambridge Universiry press, 2018)
"This book undertakes a critical reexamination of this seeming nationalist resolution of the caste question by scrutinizing the processes whereby the ironing out of caste- difference was produced and situating Mandal within them. It denaturalizes the self- evidence of Dalit integration by paying attention to how their political radicalization was contained. In so doing, it reorients the terms of reference through which Dalit politics in Bengal has been understood from preoccupations about proximity and integration with Indian nationalism, to an evaluation of the possibilities for and eventual failure of Dalit political power. My concerns are therefore trained at the specific issue of how and why the caste question, as formulated by Mandal, eventually found no fertile terrain in the east. The historical and contemporary relevance of the matter stems from the fact that wherever such politics has made its presence felt in the legislative institutions of independent India - whether the Republican Party of India or the Bahujan Samaj Party - it has done so under the sign and inspiration of Ambedkar, animated by concerns of Dalit political autonomy. An examination of Mandal's historical trajectory is therefore essential to this endeavor. I thereby share the conceit that it is equally the "spokesman who creates the group" than the other way around. As this book will suggest, the eventual failure of his political struggle, following as it did on a remarkably vibrant phase, is an instructive and meaningful one. His exceptionality is precisely what enables this revisionist attempt to tell a crucial chapter in the largely untold story of what Partha Chattopadhyay has called Bengal's 'social counter- revolution'"--